ANALISIS SWOT PADA SMAS PLUS AL-BASHARIAH KABUPATEN KOTABARU (SEBUAH STUDI KASUS) - Rudy Suryana (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2020)
This approach tries to balance the organizational organization's internal strengths and weaknesses with the external environmental opportunities and threats of existing organizations. The formulation of the problem in the study is what is the factor of strengths, weaknesses, opportunities and threats in SMA Plus Al Bashariah Kotabaru and is expected to be obtained an overview of the factors that become strengths, weaknesses, opportunities and the threats. The study used a descriptive qualitative method in which data was obtained from principals, teachers, parents. Interview, documentation and observation data collection techniques, Interactive model data analysis techniques produce strengths, weaknesses, opportunities and threats emanating from the SMAS Plus Al-Bashariah environment. The results showed the strength factor of the school is: 1) Strategic location. 2) own and adequate infrastructure. 3) High school "Plus". 4) The number & qualifications of educators and non-educators are adequate. 5) Have a clear work program. 6) Teachers have a high commitment to achievement. 7) Have an IPA Laboratory. 8) Free tuition. For identified threats to schools namely: 1). The level of public trust is low. 2) The absence of competing schools both public and private. 3) parents of students from the lower middle class economy. Keywords :SWOT analysis